Potential role of creatine as an anticonvulsant agent: evidence from preclinical studies - Alraddadi, Eman A.; Khojah, Abdulrahman M.; Alamri, Faisal F.; Kecheck, Husun K.; Altaf, Wid F.; Khouqeer, Yousef (Frontiers in Neuroscience, 2023)
Epilepsy is one of the most common neurological disorders affecting people of all ages representing a significant social and public health burden. Current therapeutic options for epilepsy are not effective in a significant proportion of patients suggesting a need for identifying novel targets for the development of more effective therapeutics. There is growing evidence from animal and human studies suggesting a role of impaired brain energy metabolism and mitochondrial dysfunction in the development of epilepsy. Candidate compounds with the potential to target brain energetics have promising future in the management of epilepsy and other related neurological disorders. Creatine is a naturally occurring organic compound that serves as an energy buffer and energy shuttle in tissues, such as brain and skeletal muscle, that exhibit dynamic energy requirements. In this review, applications of creatine supplements in neurological conditions in which mitochondrial dysfunction is a central component in its pathology will be discussed. Currently, limited evidence mainly from preclinical animal studies suggests anticonvulsant properties of creatine; however, the exact mechanism remain to be elucidated. Future work should involve larger clinical trials of creatine used as an add-on therapy, followed by large clinical trials of creatine as monotherapy.